Advanced atrioventricular block with a very prolonged ventricular asystole detected four hours after placement of an impantable loop recorder. Issue 4 (December 2016) - Korantzopoulos, P.; Ntalas, I. V.; Papafaklis, M. I.; Goudevenos, J. A.
Abstract: In this report, we present a 42‐year‐old woman without structural heart disease who underwent an implantable loop recorder implantation for recurrent syncopal episodes during the past 12 years. Four hours after implantation, the patient suffered sudden loss of consciousness while sitting on her bed in the ward. Interestingly, interrogation of the device revealed an episode of advanced atrioventricular block with a very prolonged ventricular asystole of 25 sec. We also provide a concise overview of the literature regarding the implantable loop recorder use in recurrent unexplained syncope as well as regarding idiopathic advanced atrioventricular block.